Assessment of the Network Interaction Synergistic Effect According to the Organization Life Cycle - Alona Hrebennikova; Artemchuk, Liudmyla; Nahornyi, Vitalii; Daliak, Nadiia; Ruban, Olha (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
The article’s purpose was to econometric substantiate the peculiarities of achieving a synergistic effect and sources of economies of scale for participants in entrepreneurial networks, for example, industrial enterprises in Ukraine. The regression analysis method has been used to identify sources of economies of scale of production, which change affects the efficiency of enterprises. With the elasticity coefficient, the features of the manifestation of the effect of economies of scale for 106 network and non-network enterprises were determined, taking into account the organizational life cycle of the development. It was revealed that, despite the ephemeral nature of the economies of scale, network enterprises are characterized by longer nature as a component of the synergistic effect of production activities and a decrease in costs, regardless of the development cycle of the organization. The results obtained can be useful as a basis for strategic planning in business integration.